Presence of Microplastics in the Vaquita Marina Protection Zone in Baja California, Mexico - Arely Areanely Cruz-Salas; Juan Carlos Alvarez-Zeferino; Jocelyn Tapia-Fuentes; Sheila Liliana Dafne Lobato-Rocha; Alethia Vázquez-Morillas; Sara Ojeda-Benítez; Samantha E. Cruz-Sotelo (Microplastics, 2023)
Microplastics (MP) have been evidenced in marine and coastal areas worldwide, including the Gulf of California in Mexico, where the Vaquita Marina refuge area is located, which in turn borders the protected natural area Alto Golfo de California y Delta del Rio Colorado. This research aimed to determine the concentrations of microplastics in the Vaquita protection zone, analyzing samples of ten transects of surface water and samples in the sand of five beaches on the coast surrounding the Vaquita protection polygon. The total concentrations of MP in the surface water transects were from 0.000 to 0.020 MP/m3 and their most recurrent characteristics were fragments (69.0%), the chemical composition of polyethylene (60.0%), the blue color (39.0%) and a size of 2.1–3.0 mm (31.0%). While for the beaches, these corresponded to averages ranging from 28.2 ± 36.4; 17.6 to 200.7 ± 77.9; 193.7 MP/m2, the most common characteristics of MP from beaches were filaments (33.2%), PE (32.3%), white (28.0%), and a size of 4.1–5.0 mm (32.0%). The results suggest that part of the MP on the beaches and in the Vaquita Marina refuge area could come from urban areas such as the Gulf of California and activities such as fishing. It is recommended to study all the transects of the Vaquita Marina polygon and more beaches surrounding it in different seasons to better understand the status of MP pollution.